Information systems in small and medium-sized enterprises of the textile and clothing industry - Dimitrijević Dragan; Adamović Živoslav (Tekstilna industrija, 2022)
Market uncertainty and financial instability in the era of global competition force companies to work faster and increase productivity and business efficiency with continuous cost reduction and qualitative efficiency, which serves as a basis for strengthening the competitiveness and sustainable development of all, including SMEs -small and medium-sized enterprises of the textile and clothing industry. Various innovative contents and adequate technological solutions, as well as reengineering of business/production processes, with massive and adequate implementation of technical-technological innovations based on information and communication technologies -ICT and flexible automation, i.e. on the direct and efficient implementation sector defined information systems, also represent possible elements of functional competitiveness and sustainable development. Otherwise, changes in the environment and ways of doing business of companies require a better understanding and integration of data, as well as their more efficient exploitation in the functioning and development of the company, which imposes the need for permanent generation, adaptation and development of quality and efficient information systems. As a result of such requirements, the responses of industrial production through the implementation of technical-technological innovations are inevitable, whereby quality and efficient ICT infrastructure, coherence of innovative technologies and flexible production, as well as compatibility and complementarity of production and business information systems, are necessary elements and indicators of efficiency and quality. The implementation, efficient exploitation, as well as the development of various business and production information systems, obviously has its benefits, presented through more efficient, better quality and faster operations, but also disadvantages, because it is obviously conditioned by the stochastic laws of the global market, the variable human factor or the lack of high-quality, highly educated professionals staff, requirements for high initial investments, but also the specifics of the textile/clothing industry and SMEs, as well as the incompatibility of the implemented production and business systems.